Control strategies for variable-speed permanent magnet synchronous generator systems. Issue 6 (2nd November 2015) - Shen, Jian-Xin; Miao, Dong-Min; Jin, Mengjia
Abstract : Purpose: – The purpose of this paper is to focus on various control strategies for permanent magnet synchronous generator (PMSG) systems, in order to stabilize the dc link output voltage over a wide operation speed range. Design/methodology/approach: – Two control methods, namely, the flux regulation control (FRC) which adjusts the stator flux linkage and then indirectly stabilize the dc link voltage, and the direct voltage control (DVC) which directly stabilize the dc link voltage by regulating the power angle, are proposed in this paper. Both methods can be realized by either approach of the conventional space vector pulse width modulation (SVPWM) or the proposed single voltage vector modulation (SVVM). Findings: – The FRC can optimize the field in the PMSG, however, the realization is complicated. The DVC need not estimate and regulate the stator flux linkage, hence is easy to implement. On the other hand, the SVPWM can provide smooth armature current and dc link voltage, while the SVVM applies only one voltage vector during each control cycle, hence, is simple to realize and requires the minimum switching on the PWM rectifier. All cross-combinations between the two control methods and the two realization approaches work well. Originality/value: – The proposed FRC and DVC methods are simpler than the conventional field oriented control, while the proposed SVVM is a novel and efficient approach to generate the PWM status. Optimal cross-combination, either of SVPWM-FRC, SVVM-FRC, SVPWM-DVC and SVVM-DVC, can be chosen to satisfy the system characters and requirements.